1991
DOI: 10.1080/10406639108047858
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic Conjugation in Peropyrenes

Abstract: Cyclic conjugation in benzenoid hydrocarbons is studied in the series of peropyrene and its 42 mono-, di-, tri-, tetra-, penta-and hexabenzo derivatives. Some general regularities in the conjugation pattern of these molecules are pointed out.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
2

Year Published

1993
1993
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 29 publications
1
2
2
Order By: Relevance
“…Although the central ring of the Clar picture (Figure b) has an inscribed circle, none of its six bonds are in the 1.39 Å range . The results are inconsistent with previous Hückel-type (ef-model) calculations, which concluded that the Clar structure was not sufficient to describe the π-electron structure of peropyrenes. Peropyrene ( 1 ) is more stable than its isomers rubicene ( 14 ) and benz[ e ]indeno[1,2,3,4- hi ]acephenanthrylene ( 15 ), potential peri − peri coupling products of fluorenone (an isomer of 1 ), by 115.0 and 90.3 kJ/mol, respectively.…”
contrasting
confidence: 99%
“…Although the central ring of the Clar picture (Figure b) has an inscribed circle, none of its six bonds are in the 1.39 Å range . The results are inconsistent with previous Hückel-type (ef-model) calculations, which concluded that the Clar structure was not sufficient to describe the π-electron structure of peropyrenes. Peropyrene ( 1 ) is more stable than its isomers rubicene ( 14 ) and benz[ e ]indeno[1,2,3,4- hi ]acephenanthrylene ( 15 ), potential peri − peri coupling products of fluorenone (an isomer of 1 ), by 115.0 and 90.3 kJ/mol, respectively.…”
contrasting
confidence: 99%
“…However, as we have seen, according to our modified approach, among migrating sextets the central rings are more aromatic that the terminal migrating sextets. This finding can be contrasted to findings of Polansky and Derflinger, who used HMO, which have also late been found also later by Bultinck et al who used more advanced MO calculations. According to both MO calculations the terminal migrating rings have been found to have higher local aromaticity than the central migrating rings.…”
Section: Discussioncontrasting
confidence: 76%
“…In 2005, Bultinck and coworkers generalized the Polansky index as an aromaticity measure in polycyclic aromatic hydrocarbons by considering more advanced molecular orbitals instead of the simple HMO used by Polansky and Derflinger. Below we have reproduced the Abstract of the article of Bultinck et al, published approximately 40 years after Polansky and Derflinger:
In this work, the ideas of molecular quantum similarity are used to generalize the Polansky similarity index.
…”
Section: Numerical Clar Formulasmentioning
confidence: 99%
“…Another model relating local aromaticity of polycyclic aromatic systems include harmonic oscillator model of aromaticity, and the para delocalization index (PDI) of Solà and coworkers . In addition, numerous references on aromaticity, which included among the references at the end of this article also some graph theoretical contributions, have been included. Among the letter, recent numerical representation of Clar formulas stand out as one of most important contribution, which has led to quantitative structural characterization of global and local aromaticity in benzenoid hydrocarbons …”
Section: Part 3 the Rre In Benzenoid Hydrocarbonssupporting
confidence: 83%